Kant's Transcendental Deductions: The Three Critiques and the Opus postumum - Förster, Eckart (Stanford, CA Stanford University Press, 1989)
Here are three books on the German philosopher Immanuel Kant (1724-1804), a pivotal figure in the history of Western philosophy whose attempt to synthesize the metaphysical theories on rationalism and empiricism initiated a new era of critical philosophy. Aquila attempts to move beyond Kant's work to formulate a clearer conception of his theory of cognition. He also analyzes his writings on consciousness and intuition in light of recent theories of functionalism and behaviorism and endeavors to clarify some of the more difficult aspects of the Transcendental Deduction, which deals with those ideas in consciousness produced not by intuition but by "pure reason" alone. Kant's Critique of Pure Reason began a pioneering effort to explore the content and limits of human cognition. In Kant's Transcendental Deductions , 14 of the leading Anglo-American and European Kant scholars present their research on the deductions, probably the most complex and fascinating aspects of Kant's writings. The articles trace the various forms taken by the Transcendental Deduction within the physical and metaphysical elements of Kant's work and its influence on his later political and moral writings. The intellectual revolution Kant inspired was the first, and perhaps the greatest, expression of a new approach to philosophy that sought to place human reason on a more solid foundation. According to Velkley, however, it was the philosopher Rousseau who actually prepared much of the ground for Kant's thinking, and many of his positions on questions of freedom and morality can be directly attributed to his intellectual encounter with Rousseau. This "dialogue" between Kant and Rousseau on the relationship of reason to society and human goodness has influenced European philosophers to this day. These three books would all be valuable additions to larger philosophy collections.- Raymond Frey, Bergen Comm. Coll., Paramus, N.J.Copyright 1989 Reed Business Information, Inc.
Keywords: Kant, Immanuel -- 1724-1804; 18th Century (1701-1800); Philosophy; Germany